School-based nutrition interventions for Indigenous children in Canada: a scoping review - Christina Gillies; Rosanne Blanchet; Rebecca Gokiert; Anna Farmer; Jessica Thorlakson; Laura Hamonic; Noreen D. Willows (BMC, 2020)
Abstract Background Indigenous children in Canada (First Nations, Inuit, and Métis) are disproportionately affected by nutrition-related chronic diseases such as obesity and diabetes. Comprehensive school-based nutrition interventions offer a promising strategy for improving children's access to healthy foods and sustaining positive eating behaviors. However, little is known about school-based nutrition interventions for Indigenous children. The objectives of this scoping review were to identify school-based nutrition interventions for Indigenous children in Canada and describe their components. Methods The scoping review consisted of searches in seven peer-reviewed databases and a general web search for grey literature. Eligibility criteria were applied by two reviewers, and data were extracted and charted by one reviewer using components of the comprehensive school health approach (social and physical environment, teaching and learning, policy, partnerships and services) and additional components with relevance to Indigenous interventions (cultural content, Indigenous control and ownership, funding source, evaluation). Numerical and descriptive summaries were used to present findings. Results Thirty-four unique interventions met the inclusion criteria. The majority (97%) of interventions targeted the social and physical environment, most often by offering food programs. Over half of interventions also incorporated teaching and learning (56%) and partnerships and services (59%), but fewer included a policy component (38%). Many interventions included a cultural component (56%) and most (62%) were owned and controlled by Indigenous communities (62%). Finally, over half of interventions disclosed their source(s) of funding (59%), but less than half (41%) included an evaluation component. Conclusions The review suggests that school-based interventions for Indigenous children can be more comprehensive by incorporating culturally relevant nutrition education and professional development opportunities for teachers, written school nutrition policies, and activities that actively engage families and community members. The continued focus on Indigenous control and ownership and incorporation of content specific to individual communities may enhance cultural relevancy and sustainability of interventions. Furthermore, there is a need to increase intervention evaluation and the sharing of resources related to funding. These recommendations may be used by communities, as well as by researchers and professionals working with communities, in developing comprehensive school-based nutrition interventions to improve the eating behaviors of Indigenous children.